2021
DOI: 10.1128/mbio.01548-21
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Basic Clusters in the Herpes Simplex Virus 1 Nuclear Egress Complex Drive Membrane Budding by Inducing Lipid Ordering

Abstract: Herpesviruses are large viruses that infect nearly all vertebrates and some invertebrates and cause lifelong infections in most of the world’s population. During replication, herpesviruses export their capsids from the nucleus into the cytoplasm by an unusual mechanism in which the viral nuclear egress complex (NEC) deforms the nuclear membrane around the capsid.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 141 publications
(223 reference statements)
3
42
0
Order By: Relevance
“…Consequently, site-specific Ser22-phosphorylated lamins are recognized by the cellular peptidyl-prolyl cis/trans isomerase Pin1, which isomerizes the lamins towards conformational reorganization and, thus, disassembles the lamina network to provide the capsids access to the INM [ 26 , 41 , 93 ]. Concerning the membrane-specific effects of the nuclear egress pathway, several highly valuable model systems have been established, in particular representing α-herpesvirus infections [ 6 , 7 , 94 , 95 , 96 ]. While the step toward the distinct recruitment of viral capsids to the NE is still insufficiently understood, several studies investigated the budding process in which core NEC proteins are involved by inducing membrane fission.…”
Section: Main Functionality and Regulatory Roles Shared By Herpesvira...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, site-specific Ser22-phosphorylated lamins are recognized by the cellular peptidyl-prolyl cis/trans isomerase Pin1, which isomerizes the lamins towards conformational reorganization and, thus, disassembles the lamina network to provide the capsids access to the INM [ 26 , 41 , 93 ]. Concerning the membrane-specific effects of the nuclear egress pathway, several highly valuable model systems have been established, in particular representing α-herpesvirus infections [ 6 , 7 , 94 , 95 , 96 ]. While the step toward the distinct recruitment of viral capsids to the NE is still insufficiently understood, several studies investigated the budding process in which core NEC proteins are involved by inducing membrane fission.…”
Section: Main Functionality and Regulatory Roles Shared By Herpesvira...mentioning
confidence: 99%
“…For HSV-1 and HCMV, it has been demonstrated that their heterodimeric core NECs can oligomerize to form hexameric rings, which may associate to honeycomb-like lattices and, thus, enable a membrane curvature and, subsequently, the budding of capsids [ 33 , 72 ]. In addition, specific in vitro experiments demonstrated that HSV-1 core NEC proteins are sufficient to induce a negative membrane curvature, which is an essential prerequisite for viral scission and budding [ 64 , 96 ].…”
Section: Main Functionality and Regulatory Roles Shared By Herpesvira...mentioning
confidence: 99%
“…Data of the present study indicate that formation of dimers, hexamers and higher oligomers may represent a strong intrinsic assembly property of the viral core NEC that may be significant for later steps of binding activities and regulation. Specifically, the NEC association of protein kinases, such as vCDK/pUL97, CDK1, CDK2, protein kinase C (PKC) and possibly even more, is another important characteristic shared between herpesviral NECs that leads to the phosphorylation-driven regulatory activities of the multicomponent extensions of these complexes [ 8 , 9 , 10 , 12 , 13 , 19 , 36 , 49 ]. Some of these events of site-specific phosphorylation of NEC-associated proteins have been functionally described, such as lamin A/C pSer22 phosphorylation [ 7 , 20 , 38 ], while others remain to be further investigated, such as the phosphorylation of core NEC proteins themselves, p32/gC1qR phosphorylation and the association of a variety of further phosphoproteins [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process of site-specific lamin phosphorylation is a very typical and common property of herpesviral NEC activities [ 4 , 7 , 8 ]. Beyond this, the phosphorylation of further NEC-relevant proteins is also an important hallmark of nuclear egress [ 9 , 10 , 11 , 12 ]. In our recent study, we demonstrated the oligomeric interaction of the HCMV core NEC proteins, a finding that directly referred to the hexameric NEC assemblies identified by our crystallization-based structural analyses [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being too large to egress via nuclear pores, capsids leave by budding into and then out of the perinuclear space, the former step being catalysed by the herpesvirus nuclear egress complex (NEC) [65]. A recent study identified that the NEC induces lipid ordering to generate the negative curvature required for capsid budding [66]. It is tempting to speculate that the accelerated replication kinetics of pUL21 V382E HSV-1 arises, at least in part, from an increased rate of nuclear capsid egress owing to increased Cer abundance.…”
Section: Discussionmentioning
confidence: 99%